Divergent marijuana trajectories among men: Socioeconomic, relationship, and life satisfaction outcomes in the mid-30s. (1st November 2015) - White, Helene R.; Bechtold, Jordan; Loeber, Rolf; Pardini, Dustin
Highlights: With controls, marijuana use had little effect on life functioning in adulthood. Early chronic marijuana use reduced socioeconomic attainment for Black men. Chronic marijuana users had more marijuana-using friends and partners in adulthood. Studies should consider selection effects when examining substance use outcomes. Abstract: Background: Given recent changes in marijuana policy in the United States, it is important to understand the long-term effects of marijuana use on adult functioning. We examined whether men who displayed different trajectories of marijuana use from adolescence through emerging adulthood (age ∼15–26) differed in terms of socioeconomic, social, and life satisfaction outcomes in their mid-30s. Methods: Data came from a longitudinal sample of men who were recruited in early adolescence ( N  = 506) and followed into adulthood. Four trajectory groups based on patterns of marijuana use from adolescence into emerging adulthood were compared on adult outcomes (age ∼36) before and after controlling for co-occurring use of other substances and several pre-existing confounding factors in early adolescence. The potential moderating effect of race was also examined. Results: Although there were initially group differences across all domains, once pre-existing confounds and co-occurring other substance use were included in the model, groups only differed in terms of partner and friend marijuana use. Chronic marijuana users reported the highest proportions of both. Frequent and persistent marijuana use was associated with lower socioeconomic status (SES) for Black men only. Conclusions: After statistically accounting for confounding variables, chronic marijuana users were not at a heightened risk for maladjustment in adulthood except for lower SES among Black men. Chronic users were more likely to have friends and partners who also used marijuana. Future studies should take into account pre-existing differences when examining outcomes of marijuana use.